Politics of Meaning/Meaning of Politics Cultural Sociology of the 2016 U.S. Presidential Election - Mast, Jason L.; Alexander, Jeffrey C. (Cultural Sociology,, 2019)
The 2016 U.S. presidential election revealed a nation deeply divided and in flux. This volume provides urgently needed insights into American politics and culture during this period of uncertainty. The contributions answer the election's key mysteries, such as how contemporary Christian evangelicals identified in the unrepentant candidate Trump a hero to their cause, and how working class and economically struggling Americans saw in the rich and ostentatious candidate a champion of their plight. The chapters explain how irrationality is creeping into political participation, and demonstrate how media developments enabled a phenomenon like "fake news" to influence the election. At this polarized and contentious moment, this volume satisfies the urgent need for works that carefully analyze the forces and tensions tearing at the American social fabric. Simultaneously intellectual and accessible, this volume is designed to illuminate the 2016 U.S. presidential election and its aftermath for academics and students of politics alike. .